2019
DOI: 10.7150/ijbs.38146
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-infected cell-derived exosomes promote the growth and progression of cervical cancer

Abstract: Background: Women infected with HIV are more likely to have aggressive cervical cancer, and patients with HIV infection are often more severely ill than those without HIV infection. However, the underlying mechanism for the progression of cervical cancer is not yet fully understood and requires further research. Methods: Exosomes were isolated from cell culture supernatants using differential ultracentrifugation. Confirmation of exosome isolation was based upon identification by electron microscopy and NanoSig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Interestingly, the data from the analysis by Mass Spectrometry showed that, compared to exosomes from uninfected T-cells, exosomes from HIV-1-infected T-cells are enriched in histones, RNA-binding proteins, Cdks and Src family kinases (Barclay et al, 2019). Consistent with the observation in Jin's group on HNSCC and lung cancer, it has been found that exosomes isolated from HIV-1-infected cells promote the growth and progression of cervical cancer as well (Li et al, 2019). In this study, miR-155-5p was identified as the culprit molecule in exosomes to promote the pathogenic progress of HIV-1associated cervical cancer.…”
supporting
confidence: 66%
“…Interestingly, the data from the analysis by Mass Spectrometry showed that, compared to exosomes from uninfected T-cells, exosomes from HIV-1-infected T-cells are enriched in histones, RNA-binding proteins, Cdks and Src family kinases (Barclay et al, 2019). Consistent with the observation in Jin's group on HNSCC and lung cancer, it has been found that exosomes isolated from HIV-1-infected cells promote the growth and progression of cervical cancer as well (Li et al, 2019). In this study, miR-155-5p was identified as the culprit molecule in exosomes to promote the pathogenic progress of HIV-1associated cervical cancer.…”
supporting
confidence: 66%
“…People living with HIV/AIDS may be at higher risk of cancer, which is known as HIV-associated malignancy (HAM) [100]. Traditionally, HAM is categorized into two types: AIDS-defining cancers (ADCs) and non-AIDS-defining cancers (NADCs).…”
Section: Role Of Exosomes and Hiv-associated Malignancy (Ham)mentioning
confidence: 99%
“…Although the underlying mechanism deals with the development and progression of HAM is not yet completely understood, the association between exosomes secreted from HIV-infected cells and HAM has attracted attention in recent years. Li et al investigated that exosomes from HIV-infected T lymphocytes contain miRNA-155-5p which can contribute to the advancement of cervical cancer cells via the ARID2-ERCC5-NF-κB signaling pathway and up-regulating the expression of such cytokines as IL-1, IL-6, and IL-8 [100]. Besides, Chen et al reported that TAR RNA-containing exosomes secreted from HIV-infected T-cells, by activation of the ERK1/2 signaling, may have a potential role in the development of lung cancer and HNSCC [102].…”
Section: Role Of Exosomes and Hiv-associated Malignancy (Ham)mentioning
confidence: 99%
“…Exosomes were prepared from the cell supernatants of different groups by differential ultracentrifugation as previously described [ 30 ]. In brief, the culture medium was quickly filtered to separate intact cells and debris.…”
Section: Methodsmentioning
confidence: 99%